Psychobiological markers of allostatic load in depressed and nondepressed mothers and their adolescent offspring. (21st May 2020) - Nelson, Benjamin W.; Sheeber, Lisa; Pfeifer, Jennifer; Allen, Nicholas B.
Abstract : Background: A substantial body of research has emerged suggesting that depression is strongly linked to poor physical health outcomes, which may be partly due to increased allostatic load across stress response systems. Interestingly, health risks associated with depression are also borne by the offspring of depressed persons. Our aim was to simultaneously investigate whether maternal depression is associated not only with increased allostatic load across cardiac control, inflammation, cellular aging, but also if this is transmitted to adolescent children, possibly increasing the risk for early onset of psychiatric conditions and disease in these offspring. Methods: A preregistered, case–control study of 180 low‐income mothers (50% mothers depressed, 50% mothers nondepressed) and their adolescent offspring was conducted to determine how depressed mothers and their adolescent offspring systematically differ in terms of autonomic, sympathetic, and parasympathetic cardiac control; inflammation; cellular aging; and behavioral health in offspring, which are indicators suggestive of higher allostatic load. Results: Findings indicate that depressed mothers and their adolescent offspring differ in terms of comorbid mental and physical health risk profiles that are suggestive of higher allostatic load. Findings indicate that depressed mothers exhibit elevated resting heart rate and decreased heart rate variability, and adolescent offspring of depressed mothers exhibit greater mental health symptoms, elevated heart rate, and accelerated biological aging (shorter telomeres). These effects persisted after controlling for a range of potential covariates, including medication use, sex, age, and adolescents' own mental health symptoms. Conclusions: Findings indicate that maternal depression is associated with increased allostatic load in depressed women and their adolescent children, possibly increasing risk for early onset of psychiatric conditions and disease in these offspring. Future research is needed to delineate why some biological systems are more impacted than others and to explore how findings might inform preventative programs targeted at adolescent offspring of depressed mothers.